Petrogenesis and tectonic setting of the proto-tethyan dachaidan ophiolite, North China: insights from clinopyroxene chemistry and whole-rock Sr–Nd–Pb and zircon Hf isotopes - Qu, Yilin; Liu, Xijun; Liu, Xiao; Huang, Qianwen; Yang, Qijun; Hu, Rongguo; Liu, Pengde; Song, Yujia (Frontiers in Earth Science, 2024)
IntroductionThe Dachaidan ophiolites outcrop within an ultrahigh-pressure metamorphic belt along the northern margin of the Qaidam Basin. However, their age, source, and tectonic setting remain still in debate.MethodIn this study, we investigated the geochemistry and geochronology of the Dachaidan ophiolitic gabbros.Results and DiscussionZircon U–Pb dating yielded a crystallization age of 510.0 ± 2.8 Ma and 510.0 ± 2.9 Ma for the gabbro. The gabbros have low SiO2 contents (47.15–50.10 wt.%) and high MgO contents (6.35–9.04 wt.%) and Mg# values (55–74). The total rare earth element (∑REE) contents are 8.35–28.07 ppm, lower than those of normal-type mid-ocean ridge basalts (MORBs), and the gabbros exhibit light REE depletion or flat REE patterns, with small positive Eu anomalies (Eu/Eu* = 1.06–1.40). Trace element patterns are depleted to enriched in Nb and Ta, similar to island arc rocks and MORB. Clinopyroxene thermobarometry indicates the parental magma of the gabbros formed by high-temperature (1,318°C–1,363°C) and medium-pressure (1.27–1.64 GPa) partial melting in a mantle wedge. The gabbros have depleted Sr–Nd–Pb-Hf isotopic compositions, with (87Sr/86Sr)i = 0.704586–0.707441, εNd(t) = 4.7–6.6, and zircon εHf(t) = 7.6–11.4. The age-corrected Pb isotope ratios of these volcanic rocks are variable, with 206Pb/204Pb(t) = 18.085–18.253, 207Pb/204Pb(t) = 15.595–15.614, and 208Pb/204Pb(t) = 37.880–38.148, which are similar to the isotopic compositions of typical Indian MORBs. The source of the Dachaidan ophiolite is inferred to have been depleted mantle. The Dachaidan ophiolite likely formed in a forearc oceanic setting along the northern margin of the Qaidam Basin, during the initial subduction of an oceanic plate.